1999
DOI: 10.1088/0953-8984/11/41/303
|View full text |Cite
|
Sign up to set email alerts
|

The viscosity of maltitol

Abstract: Les masses volumiques ρ(θ) de maltitol, glucose et sorbitol ont été mesurées par pycnométrie et par dilatométrie. Les variations de la masse volumique en fonction de la température sont linéaires dans la phase liquide et dans l'état vitreux. La viscosité de cisaillement a été mesurée sur 11 décades, par trois techniques: écoulement capillaire (10-1-102 Pa s), chute de bille (10-106 Pa s) et pénétromètrie (105-1012 Pa s). Elle a été ajustée suivant la relation de Vogel et la relation hyperbolique logη = A+B/(d-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Second, it may be observed from Figure 5B that the change in T -T g only induces very modest changes in k, many orders of magnitude lower than expected from the corresponding viscosity changes, which is suggested from literature to be 4-6 orders of magnitude (17)(18)(19). Thus, much more abrupt changes in inactivation rates would be expected from the simple classical interpretation of glass theory.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Second, it may be observed from Figure 5B that the change in T -T g only induces very modest changes in k, many orders of magnitude lower than expected from the corresponding viscosity changes, which is suggested from literature to be 4-6 orders of magnitude (17)(18)(19). Thus, much more abrupt changes in inactivation rates would be expected from the simple classical interpretation of glass theory.…”
Section: Discussionmentioning
confidence: 69%
“…The so-called Williams Landel Ferry (WLF) equation is one example of such a relationship (16). Measurements of the viscosity of simple mono-and disaccharides reveal that the viscosity decreases roughly 4-6 orders of magnitude when increasing the temperature 20°C above T g (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Each curve in Figure a that runs through data points is the expected decay rate for the viscous-flow mechanism: K = Fq = (γ/2η)·(2π/λ), where γ is the surface tension, η is the viscosity, and λ is the grating wavelength . For this calculation, γ is taken to be 0.063 N/m (the surface tension for glycerol), , the viscosities of sorbitol and maltitol are from ref , and the viscosity of maltose was estimated by shifting the maltitol data in temperature by their T g difference. Figure a shows that with a vertical shift, C , on the log scale (0.6 for sorbitol, −0.5 for maltitol, and −1 for maltose), the expected decay rate, Fq , well matches the observed decay constant, K .…”
Section: Resultsmentioning
confidence: 99%
“… a Notes: (1) T g is the onset temperature of glass transition measured by DSC during heating at 10 K/min. (2) The densities, ρ, are from ref (sorbitol and maltitol), ref (IMC), ref (OTP), ref (TNB), and ref (PS). The values at T g are given.…”
Section: Methodsmentioning
confidence: 99%
“…The so-called Williams-Landel-Ferry (WLF) equation is one example of such a relationship ( 31 ). Measurement of the viscosity of simple mono- and disaccharides revealed that the viscosity decreased by approximately 4 to 6 orders of magnitude when the temperature increased to 20°C above the T g ( 32 34 ). The stability of freeze-dried Lactobacillus paracasei subsp.…”
Section: Discussionmentioning
confidence: 99%